2014
DOI: 10.1161/circinterventions.114.001498
|View full text |Cite
|
Sign up to set email alerts
|

Fully Integrated High-Speed Intravascular Optical Coherence Tomography/Near-Infrared Fluorescence Structural/Molecular Imaging In Vivo Using a Clinically Available Near-Infrared Fluorescence–Emitting Indocyanine Green to Detect Inflamed Lipid-Rich Atheromata in Coronary-Sized Vessels

Abstract: Background-Lipid-rich inflamed coronary plaques are prone to rupture. The purpose of this study was to assess lipidrich inflamed plaques in vivo using fully integrated high-speed optical coherence tomography (OCT)/near-infrared fluorescence (NIRF) molecular imaging with a Food and Drug Administration-approved indocyanine green (ICG). Methods and Results-An integrated high-speed intravascular OCT/NIRF imaging catheter and a dual-modal OCT/NIRF system were constructed based on a clinical OCT platform. For imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…Previously it was thought that albumins are responsible for enhanced fluorescence in blood [8,38,41]. However, recent studies revealed that ICG might bind mainly to lipoproteins [2,8,36,42,43]. Indeed, our fluorescence measurement shows that lipoproteins bind more ICG and produce approximately three times stronger emission than albumins (Fig.…”
Section: Icg Lasing With Serological Componentsmentioning
confidence: 59%
“…Previously it was thought that albumins are responsible for enhanced fluorescence in blood [8,38,41]. However, recent studies revealed that ICG might bind mainly to lipoproteins [2,8,36,42,43]. Indeed, our fluorescence measurement shows that lipoproteins bind more ICG and produce approximately three times stronger emission than albumins (Fig.…”
Section: Icg Lasing With Serological Componentsmentioning
confidence: 59%
“…Targeted molecular agents have been used to identify lipid-rich, metabolically active plaque in rabbit arteries 155,156 . Dual-modality OCT and near-infrared autofluorescence (NIRAF) using a specialized OCT-NIRAF catheter has been shown to be feasible and safe in humans and, indeed, NIRAF enhances the sensitivity to detect vulnerable thin-cap fibroatheroma 157 .…”
Section: Molecular Techniques-mentioning
confidence: 99%
“…Studies have shown that combining angiography and intravascular ultrasound or optical coherence tomography can lead to far more information than 1 modality alone. 38,39 These fusion images are difficult to obtain and to process, but it is likely that in the future they can be real-time tools to guide diagnosis, understand pathophysiology, and guide PCI in complex anatomy. Combining imaging and hemodynamic data will also allow much more understanding of the pathophysiology of coronary disease.…”
Section: Emergence Of Intravascular Imaging and Physiology Assessmentmentioning
confidence: 99%